Analysis Of Financial Statement In Measuring Financial Performance at PT Permata Bank Tbk - Purba, Arlina Pratiwi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
This study aims to determine the bank’s financial health based on the Solvency Ratio, Profitability Ratio, and Liquidity Ratio at PT Bank Permata, Tbk. The type of data used is secondary data. The population in this study is the Statement of Financial Position and Profit and Loss Statement of PT Bank Permata Tbk, while the research sample is the Income Statement and Statement of Financial Position of PT Bank Permata Tbk for the 2017-2019 period. The data processing technique uses Financial Statement Ratios in the form of Solvency Ratios, Profitability Ratios, and Liquidity Ratio. The results of data analysis show the Solvency Ratio in the Primary Ratio, and Capital Adequacy Ratio from 2017 to 2019 based on the standard ratio set by Bank of Indonesia, it can concluded that PT Bank Permata, Tbk is in the healthy category. Profitability Ratio on Gross Profit Margin, Return on Equity Capital, Return On Assets from 2017 to 2019 based on the ratio standards set by Bank of Indonesia, it can concluded that PT Bank Permata, Tbk is in a healthy category. The liquidity ratio in the Quick Ratio, Cash ratio, and Loan to Deposit Ratio in 2017 to 2019 based on the standard ratio set by Bank of Indonesia can concluded that PT Bank Permata, Tbk is categorized as healthy